FACTORS CONTRIBUTING TO THE ANXIETY IN SPEAKING ENGLISH AMONG HIGH SCHOOL STUDENTS - Safriani, Safriani; Suryani, Suryani; Ugahara, Ugahara; Zalha, Fera Busfina (Jurnal Dedikasi Pendidikan, 2025)
The purpose of this research is to describe the primary factors contributing to high school students' anxiety when speaking English and to identify strategies that can help improve their confidence. This study employs a qualitative design with a case study approach, focusing on students at SMA 1 Kuta Baro. The sample for this study consists of six individuals selected using purposive sampling technique. And data was collected through semi structured interviews and analyzed using the Miles and Huberman (1994) framework. The findings reveal that the main causes of students' anxiety when speaking English include fear of speaking in public, lack of solutions for managing self-anxiety, and concerns about being mocked by peers. Additionally, students face difficulties due to forgetting vocabulary and fearing mispronunciations, which are often exacerbated by poor study habits and a strong Acehnese accent. These factors contribute to their struggles with speaking English fluently, frequently leading to reluctance to speak in public out of fear of making mistakes or disappointing their audience. Identified strategies to help students overcome this anxiety include expanding vocabulary, building self-confidence, preparing before speaking, using relaxation techniques, and enhancing knowledge. This research may serve as a reference for future studies on similar issues. Further research is encouraged to include classroom observations to better understand students' anxiety management and to refine interview techniques to gather more comprehensive responses